2020
DOI: 10.3389/fphys.2020.00642
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of a Rhabdomyolysis Model in Mice With Exertional Heat Stroke Mouse Model of EHS-Rhabdomyolysis

Abstract: Exertional heat stroke (EHS) is a life-threatening disease characterized by high mortality and incidence of rhabdomyolysis (RM). It would therefore be valuable to establish a stable EHS-induced RM model that accurately reflects the clinical characteristics of EHS patients and provides an objective animal model for further study of the pathogenesis of RM. In the current study, 8∼9-week-old, male, wild-type C57BL/6J mice, at the stage of sexual maturity, were randomly divided into four groups: the EHS group, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(18 citation statements)
references
References 29 publications
0
18
0
Order By: Relevance
“… 10 The mechanism by which EHS induces RM remains unclear. In the current study, using a murine EHS model, 18 we uncovered an important role of ACSL4 in mediating EHS‐induced RM. We demonstrated that EHS‐induced YAP acting through TEAD1/TEAD4 upregulates ACSL4, which, in turn, promotes lipid peroxidation, skeletal muscle cells ferroptosis, thereby, leading to loss of functional skeletal muscle cells and subsequent RM ( Figure 7 ).…”
Section: Discussionmentioning
confidence: 74%
See 4 more Smart Citations
“… 10 The mechanism by which EHS induces RM remains unclear. In the current study, using a murine EHS model, 18 we uncovered an important role of ACSL4 in mediating EHS‐induced RM. We demonstrated that EHS‐induced YAP acting through TEAD1/TEAD4 upregulates ACSL4, which, in turn, promotes lipid peroxidation, skeletal muscle cells ferroptosis, thereby, leading to loss of functional skeletal muscle cells and subsequent RM ( Figure 7 ).…”
Section: Discussionmentioning
confidence: 74%
“…In this study, using the previous established murine EHS model, 18 we demonstrate that YAP, acting through TEAD1/TEAD4 relevant Hippo signalling, mediated EHS‐induced upregulation of ACSL4 which in turn, increased lipid peroxiadation level, as well as skeletal muscle cell ferroptosis and subsequent augmented skeletal muscle tissue injury. Inhibition of YAP, pharmacological inhibition of ACSL4, or blocking lipid peroxidation prevented EHS‐induced ferroptosis and ameliorated skeletal muscle tissue injury.…”
Section: Introductionmentioning
confidence: 66%
See 3 more Smart Citations